Empowering leadership, uncertainty avoidance, trust, and employee creativity: Interaction effects and a mediating mechanism - Zhang, Xiaomeng; Zhou, Jing (Organizational behavior and human decision processes, 2014)
•Empowering leadership, uncertainty avoidance, trust interacted to affect creativity.•The relations was strongest when uncertainty avoidance and trust were both high.•The interactional approach guided us to theorize the three-way interaction.•Creative self-efficacy mediated the three-way interaction and creativity. Taking an interactional approach, we hypothesized that (a) there is an interaction between empowering leadership, uncertainty avoidance, and trust that affects creativity, such that empowering leadership has the strongest positive relationship with creativity when the employees have high levels of uncertainty avoidance and trust their supervisors; and (b) creative self-efficacy mediates the effect that this three-way interaction between empowering leadership, uncertainty avoidance and trust has on creativity. In Study 1, we used a time-lagged research design, collecting multi-source data from 322 employees and their supervisors. The results of Study 1 supported our hypotheses. In Study 2, we used a more temporally rigorous research design in which data were collected in three stages, with a two-month time interval separating Stages 1 and 2, and Stages 2 and 3. On the basis of the time-lagged and multi-source data from 199 employees and their supervisors, Study 2 produced the same results as Study 1. We discuss the implications of these results for future research and practice.